Esthetic anterior resin restorations: to bevel enamel or not? : to bevel enamel or not? = Restauraciones estéticas de resina en dientes anteriores : biselar el esmalte o no? - Ramírez Barrantes, Juan Carlos 1964-
Restoration of fractured anterior teeth presents a challenge to dental clinicians owing to its esthetic requirements and, more importantly, because of the young age of the patients. Thus, it is important to follow the most conservative protocol. Many professionals face the dilemma of whether or not to perform enamel beveling. This article briefly discusses the clinical perspective and evidence regarding this type of operative restoration procedure.